Monolithic Fabrication of NPN/SiNx Dual Membrane Cavity for Nanopore‐Based DNA Sensing. Issue 14 (29th May 2019) - Madejski, Gregory R.; Briggs, Kyle; DesOrmeaux, Jon‐Paul; Miller, Joshua J.; Roussie, James A.; Tabard‐Cossa, Vincent; McGrath, James L.
Abstract: Nanoscale preconfinement of DNA is shown to reduce the variation of passage times through solid‐state nanopores. Preconfinement is previously achieved by forming a femtoliter‐sized cavity capped with a highly porous layer of nanoporous silicon nitride (NPN). This cavity is formed by sealing a NPN nanofilter membrane against a substrate chip using water vapor delamination. Ultimately, this method of fabrication cannot keep a consistent spacing between the filter and solid‐state nanopore due to thermal fluctuations and wrinkles in the membrane, nor can it be fabricated on thousands of individual devices reliably. To overcome these issues, a method is presented to fabricate the femtoliter cavity monolithically, using a selective xenon difluoride (XeF2 ) etch to hollow out a polysilicon (poly‐Si) spacer sandwiched between silicon nitride (SiN x ) layers. These monolithically fabricated cavities behave identically to their counterparts formed by vapor delamination, exhibiting similar translocation passage time variation reduction and folding suppression of DNA without requiring extensive manual assembly. The ability to form nanocavity sensors with nanometer‐scale precision and to reliably manufacture them at scale using batch wafer processing techniques will find numerous applications, including motion control of polymers for single‐molecule detection applications, filtering of dirty samples prior to nanopore detection, and simple fabrication of single‐molecule nanobioreactors. Abstract : Monolithically fabricated femtoliter cavities demonstrate reduction in coefficient of variation for DNA translocation. The cavities are created from the extreme selectivity of xenon difluoride (XeF2 ) to polysilicon (poly‐Si) over silicon nitride (SiN x ). Precise depositions of a SiN x /poly‐Si/SiN x thin film stack create well‐defined spacings between a porous prefilter and sensing nanopore layer, improving the yield and consistency of devices over manually created cavities.